Using Flow Cytometry to Measure Phagocytic Uptake in Earthworms - Sheryl L. Fuller-Espie (American Society for Microbiology, 2010)
This laboratory module familiarizes students with flow cytometry while acquiring quantitative reasoning skills during data analysis. Leukocytes, also known as coelomocytes (including hyaline and granular amoebocytes, and chloragocytes), from Eisenia hortensis (earthworms) are isolated from the coelomic cavity and used for phagocytosis of fluorescent Escherichia coli. Students learn how to set up in vitro cellular assays and become familiar with theoretical principles of flow cytometry. Histograms based on fluorescence and scatter properties combined with gating options permit students to restrict their analyses to particular subsets of coelomocytes when measuring phagocytosis, a fundamentally important innate immune mechanism used in earthworms. Statistical analysis of data is included in laboratory reports which serve as the primary assessment instrument.